Preparation of B4Cp/Al Composites via Selective Laser Melting and Their Tribological Properties - Yang, Guodong; Zhang, Jialian; Xie, Houbo; Li, Faliang; Huang, Zhong; Yuan, Gaoqian; Zhang, Jingzhe; Jia, Quanli; Zhang, Haijun; Yeprem, Hasibe Aygul; Zhang, Shaowei (MDPI, 2022)
B4C-particle-reinforced Al (B4Cp/Al) composites are widely used in various areas, e.g., armors, electronic packaging and fuel storage, owing to their several outstanding properties including high specific rigidity, excellent wear resistance and light weight. Selective laser melting (SLM) is favored in manufacturing complex components because of its high raw material utilization rate and high efficiency. In this work, a B4Cp/Al composite was successfully synthesized by SLM, and the effects of one of the most important parameters, scanning speed (100-700 mm/s), on the phase composition, density, microhardness and tribological properties of the samples were investigated. The microhardness, relative density and dry-sliding wear resistance of as-prepared B4Cp/Al composites were improved with the decrease in scanning speed, and the sample fabricated at a scanning speed of 100 mm/s exhibited a relative density as high as about 97.1%, and a maximum microhardness of similar to 180 HV0.1 (approximately six times more than that of the SLM-formed pure Al sample, 31 HV0.1), a minimum wear rate of 4.2 x 10(-5) mm(3)center dot N-1 center dot m(-1) and a corresponding friction coefficient of 0.41. In addition, abrasive wear, adhesive wear and oxidation wear were found to be behind the overall wear behavior of as-prepared B4Cp/Al composites.
Keywords: selective laser melting; B4Cp/Al composites; scanning speed; relative density; tribological property; MECHANICAL-PROPERTIES; STAINLESS-STEEL; TEXTURE EVOLUTION; PARTICLE-SIZE; AL; MICROSTRUCTURE; MATRIX; B4C; FABRICATION; ALUMINUM; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics